Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

18x3 + 6x2y - 9x2 - 3xy

factor completely


Sagot :

Answer:

[tex]\sf 3x(3x+y)(2x-1)[/tex]

Step-by-step explanation:

Given expression:

[tex]\sf 18x^3 + 6x^2y - 9x^2 - 3xy[/tex]

Factor out common term [tex]\sf 3x[/tex]:

[tex]\sf \implies 3x(6x^2 + 2xy - 3x - y)[/tex]

Factor [tex]\sf (6x^2 + 2xy - 3x - y)[/tex]

Rearrange:

[tex]\sf \implies 6x^2 - 3x+ 2xy - y[/tex]

Factor pairs of terms:

[tex]\sf \implies 3x(2x-1)+ y(2x - 1)[/tex]

Factor out common term (2x - 1):

[tex]\sf \implies (3x+y)(2x-1)[/tex]

Final solution:

[tex]\sf \implies 3x(3x+y)(2x-1)[/tex]